Comparative method in teaching Turkish as a foreigen language - Čaušević, Ekrem (2007)
In one of the bulletins presented in the symposium organized by TÖMER on 11-13 May 2000, there was a comment suggesting that "There are various methods facilitating Turkish teaching, however there is no best method". Even if this comment is right, we would like to talk about the advantages of a specific method in this bulletin. This method is based on comparing the foreign language to the native language of the student. It is obvious that this method, which improves the cognitive ability of the student learning Turkish at faculty level whose native language is not Turkish, is based on comparative grammar.
Projekt MZOS
ENG